IL-1 beta is induced in reactive astrocytes in the somatosensory cortex of rats with genetic absence epilepsy at the onset of spike-and-wave discharges, and contributes to their occurrence - ONAT, FİLİZ; GÜLHAN, REZZAN (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2011)
Interleukin (IL)-1 beta plays a crucial role in the mechanisms of limbic seizures in rodent models of temporal lobe epilepsy. We addressed whether activation of the IL-1 beta signaling occurs in rats with genetic absence epilepsy (GAERS) during the development of spike-and-wave discharges (SWDs). Moreover, we studied whether inhibition of IL-1 beta biosynthesis in GAERS could affect SWD activity. IL-1 beta expression and glia activation were studied by immunocytochemistry in the forebrain of GAERS at postnatal days (PN)14, PN20, and PN90 and in age-matched non-epileptic control Wistar rats. In PN14 GAERS, when no SWDs have developed yet. UT immunostaining was undetectable, and astrocytes and microglia showed a resting phenotype similar to control Wistar rats. In 3 out of 9 PN20 GAERS, IL-1 beta was observed in activated astrocytes of the somatosensory cortex; the cytokine expression was associated with the occurrence of immature-type of SWDs. In all adult PN90 GAERS, when mature SWDs are established, IL-1 beta was observed in reactive astrocytes of the somatosensory cortex but not in adjacent cortical areas or in extra-cortical regions. An age-dependent c-fos activation was found in the somatosensory cortex of GAERS with maximal levels reached in PN90 rats; c-fos was also induced in some thalamic nuclei in PN20 and PN90 GAERS. Inhibition of IL-1 beta biosynthesis in PN90 GAERS by 4-day systemic administration of a specific ICE/Caspase-1 blocker, significantly reduced both SWD number and duration. These results show that IL-1 beta is induced in reactive astrocytes of the somatosensory cortex of GAERS at the onset of SWDs. IL-1 beta has pro-ictogenic properties in this model, and thus it may play a contributing role in the mechanisms underlying the occurrence of absence seizures. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Inflammation; Absence seizures; Interleukins; SWD; EXPERIMENTAL FEBRILE SEIZURES; STATUS EPILEPTICUS; GLUTAMATE UPTAKE; EPILEPTOGENESIS; EXPRESSION; MODEL; ACTIVATION; INTERLEUKIN-1-BETA; HIPPOCAMPUS; CYTOKINES